Pengaruh Peer Support dan Kepuasan Kerja Terhadap Kinerja Karyawan dengan Komitmen Organisasional Sebagai Mediator pada Karyawan Gen Z PT Shuton Majalengka - Derih, Derih; Hartono, Edy; M Siddiq, Dedi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This research examines the influence of peer support and job satisfaction on employee performance, with organizational commitment as a mediating variable, focusing on Generation Z employees at PT Shuton Majalengka. The study addresses the growing need for organizations to optimize the potential of Generation Z, who have distinct work characteristics shaped by technological literacy and evolving workplace values. Using a quantitative approach, data were collected through questionnaires distributed to selected respondents. The sampling technique employed was purposive sampling, targeting employees who met the predetermined criteria. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method to test the direct and indirect relationships between variables. The findings of this research are expected to contribute both theoritically, by expanding the literature on human resource management in the context of Generation Z, and practically, by providing recommendations for enhancing employee performance through improved peer support, job satisfaction, and organizational commitment..